Tragedy as Contingency Acknowledgement: Towards a Practical Religious-Scientific Theory - Dalen, Egbert van (Journal of empirical theology, 2019)
According to philosopher of religion Kurt Wuchterl, contingency acknowledgement (German: Kontingenzanerkennung) means that rational thinking is inadequate for explaining contingency experiences. The authors argue that, in the tragic narrative of a contingency experience, subjects face limitations in three dimensions: in the individual, social and transcending dimensions. The individual dimension is expressed in powerful, visual metaphors for the confrontation with forces that do not take the human dimension into account in any way, even coercing the subjects to relinquish their existence. The social dimension concerns the tragic subject's feeling of being avoided and excluded by some individuals in their environment. The transcending dimension emerges in the complaint "Why me?", which religious persons address to a religious power, using moral arguments. Empirical research suggests that the acknowledgement of one's own limitations resulting from a contingency experience can be seen as a sign of strength rather than weakness, for, by doing so, one shows the courage to let go of past interpretative frameworks and be vulnerable. This creates the possibility of an opening in the interpretation crisis, which can lead to an unexpected, new perspective.